Effect of protective atmospheres on physicochemical, microbiological and rheological characteristics of sliced Mozzarella cheese - Olivares, María Laura (2012)
Mozzarella cheese slices packaged in bags of polyvinylidene chloride under vacuum (V) and using a gas mixture of equal parts of CO 2 and N 2 (G) were stored at 4°C for 8 weeks and analysed at different storage times by physicochemical, microbiological and rheological characterization. Expected values of moisture, total nitrogen, soluble nitrogen at pH 4.6, and chloride contents and of pH were observed. The degradation of α s1-casein was greater than β-casein degradation, while no significant differences were observed due to the packaging methods. Coliform microorganisms were not detected, while levels of moulds and yeasts counts were acceptable. Expected values of total mesophile counts were obtained. The temperature at crossover moduli (T c) was determined from temperature sweeps carried out by rheometry. Greater values of T c were observed in samples G. The influence of temperature on complex viscosity was studied by an Arrhenius-type equation. Activation energy values were obtained from the solid-like region (20-40°C) and liquid-like region (40-60°C). A more rapid change in viscosity with temperature was observed when storage time increased and when storage method V was used. © 2012 Elsevier Ltd.